2010
DOI: 10.1084/jem.20100575
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanism for the generation of human xeno-autoantibodies against the nonhuman sialic acid N-glycolylneuraminic acid

Abstract: The nonhuman sialic acid N-glycolylneuraminic acid (Neu5Gc) is metabolically incorporated into human tissues from certain mammalian-derived foods, and this occurs in the face of an anti-Neu5Gc “xeno-autoantibody” response. Given evidence that this process contributes to chronic inflammation in some diseases, it is important to understand when and how these antibodies are generated in humans. We show here that human anti-Neu5Gc antibodies appear during infancy and correlate with weaning and exposure to dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
150
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 139 publications
(161 citation statements)
references
References 60 publications
5
150
1
Order By: Relevance
“…Unlike adult humans, Cmah(−/−) mice do not have circulating antibodies against Neu5Gc (19). However, they can be immunized against Neu5Gc using a mechanism similar to that which induces human anti-Neu5Gc antibodies: incorporation of Neu5Gc into the lipo-oligosaccharides of the human-specific commensal microbe Haemophilus influenzae (17). As with humans, immunization with this Neu5Gc-expressing bacterium generates an antiNeu5Gc response that varies among individual Cmah(−/−) mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike adult humans, Cmah(−/−) mice do not have circulating antibodies against Neu5Gc (19). However, they can be immunized against Neu5Gc using a mechanism similar to that which induces human anti-Neu5Gc antibodies: incorporation of Neu5Gc into the lipo-oligosaccharides of the human-specific commensal microbe Haemophilus influenzae (17). As with humans, immunization with this Neu5Gc-expressing bacterium generates an antiNeu5Gc response that varies among individual Cmah(−/−) mice.…”
Section: Resultsmentioning
confidence: 99%
“…1). Human antibody profiles against Neu5Gc are varied in level and composition, but all humans have circulating antibodies against Neu5Gc, which appear early in life (15)(16)(17). The antibody repertoire of females also extends to their reproductive tract, through which the sperm must pass and in which embryos must implant (18).…”
mentioning
confidence: 99%
“…However, besides α-Gal, a sialic acid named Neu5Gc is the only mammalian carbohydrate present in high amounts in beef, lamb, pork, and cow's milk [36]. Similar to α-Gal, Neu5Gc is found in most mammals including primates [37] but not in humans due to a mutation in the gene encoding the enzyme responsible for Neu5Gc synthesis.…”
Section: Features Of the Immune Response To Carbohydratesmentioning
confidence: 99%
“…Intriguingly, the steep increase of MS prevalence in Japan after World War II has been attributed to the replacement of the Neu5GC-poor traditional Japanese food by the Neu5GC-rich Western diet (Yamamura and Miyake, 2013). Experiments in CMAHdeficient mice have shown that dietary Neu5Gc is incorporated in the gut flora and in the glycocalyx of various body tissues (Taylor et al, 2010). The dietary modified gut flora induces the production of heterophilic antibodies, which can bind Neu5Gc incorporated in tissue glycocalyx and in this way interfere with cellular interactions and communication (Taylor et al, 2010;Samraj et al, 2014).…”
Section: Modeling the Cause Of The Primary Lesionmentioning
confidence: 99%
“…Experiments in CMAHdeficient mice have shown that dietary Neu5Gc is incorporated in the gut flora and in the glycocalyx of various body tissues (Taylor et al, 2010). The dietary modified gut flora induces the production of heterophilic antibodies, which can bind Neu5Gc incorporated in tissue glycocalyx and in this way interfere with cellular interactions and communication (Taylor et al, 2010;Samraj et al, 2014).…”
Section: Modeling the Cause Of The Primary Lesionmentioning
confidence: 99%